Systematic and Multi-Omics Prognostic Analysis of Lysine Acetylation Regulators in Glioma - Tu, Zewei; Wu, Lei; Luo, Haitao; Li, Jingying; Lv, Shigang; Ye, Minhua; Liu, Feng; Tao, Chuming; Zhu, Xingen; Huang, Kai (Frontiers in Molecular Biosciences, 2021)
Lysine acetylation modification, which has key roles in maintaining cellular homeostasis as well as cancer malignancy, is dynamically regulated by lysine acetylation regulators (LARs). In our study, we found that most of 33 evaluated LARs were differentially expressed among 905 gliomas grouped by different clinicopathological characteristics. Consensus clustering was applied to 33 LARs, resulting in three stratified glioma subtypes (LA1, 2, and 3). The LA3 subgroup was associated with the poorest clinical outcome, highest WHO grade, fewer isocitrate dehydrogenase (IDH) mutations, and lower frequency of 1p/19q codeletion. Furthermore, gene set enrichment analysis (GSEA) indicated that eight tumor hallmarks were highly enriched in the LA3 subgroup. These results suggested that LARs are significantly related to glioma malignancy. We then designed a risk signature based on 14 overall survival (OS)-related LARs, and showed that the risk signature possesses strong and independent prognostic value for glioma patients in both training and validation datasets. Moreover, by interrogating single nucleotide polymorphism (SNP) and copy number variation (CNV) data in The Cancer Genome Atlas (TCGA) dataset, we found that higher score of our risk signature is correlated with the hypermutation status of gliomas and that HDAC1(1p) was one of the oncogenes lost in 1p/19q codeletion events, while SIRT2(19q) and EP300(22q) may act as tumor suppressors in gliomas with 19q or 22q deletions, respectively. In conclusion, LARs are critical for the malignant development of gliomas, and our results may be useful for prognostic stratification and development of novel therapeutic strategies for the treatment of glioma patients.